THE EFFECT OF WARM COMPRESSES OF RED GINGER ON REDUCING PAIN IN RHEUMATOID ARTHRITIS - Nur Isriani Najamuddin Nur Isriani; Iis Ismayanti; Andan Firmansyah; Elis Noviati (Bina Generasi : Jurnal Kesehatan, 2022)
Introduction : Pain is one of the physiological problems that can be found in Rheumatoid Arthritis patients. An effort that can be made to solve the problem is a warm compress of red ginger. Methods : This study uses a case study design with a nursing care approach or the implementation of evidence-based practice that focuses on nursing innovation. This research was carried out in Cikanyere Hamlet RT/003 RW/014 Gegempalan Village, the working area of the UPTD Cikoneng Health Center on May 25-28, 2022. Participants in this study were one family with a family member who experienced pain, namely Mrs.K aged 67 years, with complaints of pain in the right knee joint. Data collection techniques in this study include interviews, observations, physical examinations and documentation studies. Results : The client said there was an effect of warm ginger compresses on the pain he felt, with the results of the pain scale before being given the intervention of warm compresses of red ginger by 4 (1-10) with indications of moderate pain, and after being given the intervention of warm compresses of red ginger by 2 (1-10) with indications of mild pain. Discussion : Giving of warm compresses of red ginger is effective in lowering pain in clients with Rheumatoid Arthritis, this intervention can be done independently by the client. Keywords: Pain, Rheumatoid Arthritis, warm compresses of red ginger